Cytotoxicity of β-tricalcium phosphate chitosan gelatin composite scaffold as a bone substitute: in vitro study - Putri, Tansza Setiana; Eddy, Eddy; Pratiwi, Deviyanti; Kurniawan, Florencia Livia; Swe, Thet Thet (Padjadjaran Journal of Dentistry, 2026)
Introduction: Beta-tricalcium phosphate (βTCP) has higher solubility than hydroxyapatite (HA), allowing it to be more easily resorbed and replaced by newly formed bone. This higher solubility enables the release of calcium and phosphate ions that play important roles in bone remodeling and osteoblast activity; however, excessive ion release may lead to cytotoxic effects. Limestone, mainly composed of calcium carbonate (CaCO₃), can serve as a calcium source for the fabrication of βTCP. βTCP scaffolds can be combined with organic components such as chitosan and gelatin to form composite scaffolds for bone tissue engineering. Therefore, this study aimed to analyze the cytotoxicity of a β-tricalcium phosphate–chitosan–gelatin composite scaffold as a bone substitute. Methods: Type of research was experimental laboratory. Freeze-drying method was used to produce a composite scaffold which was divided into two groups: chitosan-gelatin scaffold as control group and βTCP-chitosan-gelatin scaffold (each group consisted of three samples) To evaluate cytotoxicity, composite scaffolds were tested on osteoblast cells and the MTT assay was measured and assessed based on time evaluation at 24 hours and 72 hours. Cytotoxicity was determined based on the percentage of viable cells obtained from the MTT assay. Results: Viable cells percentage on the chitosan-gelatin scaffold was 70.32% at 24 h and increased to 99.52% at 72 h. While on the chitosan-gelatin-βTCP scaffold there were 85.11% viable cells at 24 h and increased to 89.54% at 72 h. Statistical analysis using one-way ANOVA showed no significant difference among all groups (p>0.05). However, Fisher’s LSD test indicated a significant difference in cell viability between 24 hours and 72 hours within the chitosan gelatin group. Conclusion: The βTCP-chitosan-gelatin composite scaffold demonstrated no cytotoxic effect on osteoblast cells, indicating its biocompatibility and potential suitability as a bone substitute material.